Suppression of Escherichia coli Growth Dynamics via RNAs Secreted by Competing Bacteria - Markelova, Natalia; Glazunova, Olga; Alikina, Olga; Panyukov, Valeriy; Shavkunov, Konstantin; Ozoline, Olga (Frontiers in Molecular Biosciences, 2021)
With the discovery of secreted RNAs, it has become apparent that the biological role of regulatory oligonucleotides likely goes beyond the borders of individual cells. However, the mechanisms of their action are still comprehended only in general terms and mainly for eukaryotic microRNAs, which can interfere with mRNAs even in distant recipient cells. It has recently become clear that bacterial cells lacking interference systems can also respond to eukaryotic microRNAs that have targets in their genomes. However, the question of whether bacteria can perceive information transmitted by oligonucleotides secreted by other prokaryotes remained open. Here we evaluated the fraction of short RNAs secreted by Escherichia coli during individual and mixed growth with Rhodospirillum rubrum or Prevotella copri, and found that in the presence of other bacteria E. coli tends to excrete oligonucleotides homologous to alien genomes. Based on this observation, we selected four RNAs secreted by either R. rubrum or P. copri, together with one E. coli-specific oligonucleotide. Both fragments of R. rubrum 23S-RNA suppressed the growth of E. coli. Of the two fragments secreted by P. copri, one abolished the stimulatory effect of E. coli RNA derived from the 3’-UTR of ProA mRNA, while the other inhibited bacterial growth only in the double-stranded state with complementary RNA. The ability of two RNAs secreted by cohabiting bacteria to enter E. coli cells was demonstrated using confocal microscopy. Since selected E. coli-specific RNA also affected the growth of this bacterium, we conclude that bacterial RNAs can participate in inter- and intraspecies signaling.